Pengaruh Permainan Ular Tangga terhadap Pengenalan Angka di Taman Kanak-Kanak Melati Ikhlas Nanggalo Kota Padang - Kurnia, Winda Desti; Rakimahwati, Rakimahwati (Darul Yasin Al Sys, 2023)
This research is motivated by the problem of using monotonous media that often does not even use media in the learning process, this study aims to determine the effect of snakes and ladders games on number recognition at Melati Ikhlas Kindergarten Nanggalo Padang City. This type of research is quantitative with experimental methods in the form of quasy experimental (pseudo-experiment). And the sampling technique uses purposive sampling technique. The study population was 88 children, while the sample was 18 children as a control class. The research instrument consists of five items with score categorization BB (1), MB (2), BSH (3) and BSB (4). The data analysis technique uses normality test, homogeneity test, hypothesis test, with the help of computerized SPSS 25. Based on the results of the study, it shows that the data is normally distributed and homogeneous, so then hypothesis testing is carried out. Hypothesis testing aims to see if there is an effect of treatment in each class. Hypothesis testing was carried out using the independent sample test. There is a difference in the average score increase in the experimental class and control class. The increase in children's scores was higher in the experimental class with an increase of 160 scores, while in the control class the increase was 151 scores. So the results showed that there was an effect of snakes and ladders game on number recognition at Melati Ikhlas Kindergarten Nanggalo Padang City.